Antioxidant, cytotoxic, and antimicrobial activities of Glycyrrhiza glabra L., Paeonia lactiflora Pall., and Eriobotrya japonica (Thunb.) Lindl. extracts - Zhou, Junxian; Braun, Markus S.; Link, Pille; Wetterauer, Bernhard; Wink, Michael (Medicines, 2019)
Background: The phytochemical composition, antioxidant, cytotoxic, and antimicrobial activities of a methanol extract from Glycyrrhiza glabra L. (Ge), a 50% ethanol (in water) extract from Paeonia lactiflora Pall. (Pe), and a 96% ethanol extract from Eriobotrya japonica (Thunb.) Lindl. (Ue) were investigated. Methods: The phytochemical profiles of the extracts were analyzed by LC-MS/MS. Antioxidant activity was evaluated by scavenging 2,2-diphenyl-1-picrylhydrazyl (DPPH) and 2,2-azino-bis (3-ethylbenzothiazoline-6-sulphonic acid) (ABTS) radicals and reducing ferric complexes, and the total phenolic content was tested with the Folin–Ciocalteu method. Cytotoxicity was determined with a 3-(4,5-dimethylthiazol-2-yl)-2,5-diphenyltetrazolium bromide (MTT) assay in murine macrophage RAW 264.7 cells. Antimicrobial activity of the three plant extracts was investigated against six bacterial strains with the broth microdilution method. Results: Only Pe showed high antioxidant activities compared to the positive controls ascorbic acid and (−)-epigallocatechin gallate (EGCG) in DPPH assay; and generally the antioxidant activity order was ascorbic acid or EGCG > Pe > Ue > Ge. The three plant extracts did not show strong cytotoxicity against RAW 264.7 cells after 24 h treatment with IC50 values above 60.53 ± 4.03 μg/mL. Ue was not toxic against the six tested bacterial strains, with minimal inhibitory concentration (MIC) values above 5 mg/mL. Ge showed medium antibacterial activity against Acinetobacter bohemicus, Kocuria kristinae, Micrococcus luteus, Staphylococcus auricularis, and Bacillus megaterium with MICs between 0.31 and 1.25 mg/mL. Pe inhibited the growth of Acinetobacter bohemicus, Micrococcus luteus, and Bacillus megaterium at a MIC of 0.08 mg/mL. Conclusions: The three extracts were low-cytotoxic, but Pe exhibited effective DPPH radical scavenging ability and good antibacterial activity; Ue did not show antioxidant or antibacterial activity; Ge had no antioxidant potential, but medium antibacterial ability against five bacteria strains. Pe and Ge could be further studied for their potential to be developed as antioxidant or antibacterial candidates.